2021
DOI: 10.33158/asb.r116.v6.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neural network and canonical interrelationships for the physiological aspects of soybean seedlings: effects of seed treatment

Abstract: The objective of this work was to analyze the performance of soybean seedlings in different seed treatments, with multivariate profiles and canonical interrelationships. The experiment was conducted in the county of Mineiros-GO. The soil was classified as a Quartzarenic Neosol. The experimental design used was a randomized block in a 5x4 factorial, corresponding to the seed treatments (WAT, CRU, FIP, FOR and STA) in 4 soybean cultivars (Bônus, Ultra, Extra and BKS7830), in 4 repetitions. Before sowing, pre-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…The analysis of variance summary with the mean square MS and significance by the F test revealed significant interaction between cultivar x seed treatment in all variables (p <0.01) (Table 3). The results found corroborate with Moraes Dan, Almeida, Piccinin, Ricci and Ortiz (2012), Mattos et al (2018), Silva, Oliveira and Neres (2018) and Ferreira et al (2020), when diagnosing changes in the means of their respective works. Based on the results found in Table 4, it was observed that the SDI in cv.…”
Section: Resultssupporting
confidence: 86%
“…The analysis of variance summary with the mean square MS and significance by the F test revealed significant interaction between cultivar x seed treatment in all variables (p <0.01) (Table 3). The results found corroborate with Moraes Dan, Almeida, Piccinin, Ricci and Ortiz (2012), Mattos et al (2018), Silva, Oliveira and Neres (2018) and Ferreira et al (2020), when diagnosing changes in the means of their respective works. Based on the results found in Table 4, it was observed that the SDI in cv.…”
Section: Resultssupporting
confidence: 86%
“…Soybean is one of the main crops of agriculture, with a relevant socioeconomic role, with Brazil being the second largest world producer of oilseeds. In the 2018/2019 harvest, the crop occupied an area of 35.8 million hectares in the country, with a 1.9% increase in planted area compared to the previous harvest, with an estimated production of 114.4 million tons of grains (Companhia Nacional de Abastecimento [CONAB], 2019;Hanyu, Costa, Cecon, & Matsuo, 2020;Soares, Sediyama, & Matsuo, 2020;Ferreira et al, 2020;Frota et al, 2020;Carvalho et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean plants are affected by various abiotic stresses such as high salinity, low temperatures, mineral element toxicity, drought and others (Ferreira et al, 2020;Escalera et al, 2021;Gontijo et al, 2021;Pimentel et al, 2021). Drought or continuous water deficiency is one of the most important factors affecting growth, development, survival and productivity of the crop (Manavalan, Guttikonda, Tran, & Nguyen, 2009;Fried, Narayanan, & Fallen, 2019).…”
Section: Introductionmentioning
confidence: 99%